Enhancer Profiling Reveals a Protective Role of RXRα Against Calcium Oxalate‐Induced Crystal Deposition and Kidney Injury - Yu Yang; Xudan Dou; Yongzhan Sun; Mengyao Wang; Jing Wang; Xinyi Cao; Haijie Xie; Linguo Xie; Weiping Tian; Jing Nie; Yupeng Chen; Chunyu Liu; et al. (Advanced Science)
Abstract During the formation of kidney stones, the interaction between crystals and tubular epithelial cells (TECs) leads to tubular injury and dysfunction, which in turn promote stone formation. However, the molecular mechanisms underlying these changes in TECs remain elusive. Drug screening revealed that JQ1 inhibited the adhesion of calcium oxalate (CaOx) crystals to TECs. Its therapeutic effect is further confirmed in a glyoxylic acid‐induced CaOx crystal deposition mouse model. Utilizing epigenomic and transcriptomic profiling, dynamic enhancer landscape and gene expression program associated with nephrolithiasis are charted. Bioinformatic analysis pinpointing the RXRα as a central transcription factor (TF) modulating enhancer activity. Importantly, the animal studies revealed that RXRα deletion promoted the CaOx crystal deposition, while its activation by Bexarotene (Bex), an FDA‐approved drug, mitigated this progression. Mechanistically, under normal circumstances, RXRα inhibited nephrolithiasis‐promoting genes by recruiting the HDAC3/SMART complex to repress enhancer activity. Yet, with the progression of CaOx crystal deposition, RXRα expression decreased, leading to enhancer activation and subsequent upregulation of nephrolithiasis‐promoting genes. In summary, the work illustrates an epigenetic mechanism underlying TECs fate transition during CaOx crystal deposition and highlights the therapeutic potential of JQ1 and Bex in managing kidney stone diseases.